Cancer and Accelerated Aging Research at the National Institutes of Health, 2013–2023: A Grant Portfolio Analysis. - Gallicchio, Lisa; Brick, Rachelle; Tesauro, Gina; Page, Lindsey; Green, Paige; Guida, Jennifer L. (Journal of the American Geriatrics Society, 2025)
Background: The purpose of this study was to describe the characteristics of the NIH‐funded grant portfolio focused on cancer and accelerated aging. Methods: Research project grants focused on cancer survivors and aging trajectories that were newly funded during fiscal years 2013 through 2023 were identified by first using a text mining algorithm from the NIH Research, Condition, and Disease Categorization (RCDC) system with cancer survivorship‐relevant terms and then a list of aging‐related terms that included aging, neurocognition, and physical function. Included grants were double coded to extract study characteristics. Results: A total of 166 grants were identified, with the National Cancer Institute (NCI) and National Institute on Aging (NIA) funding 62.0% and 23.5% of the grants, respectively. The number of newly funded grants rose from nine in 2013 to 27 in 2023. Overall, the majority were observational studies (65.1%); 45% included study samples of multiple cancer types. The most commonly examined outcomes were cognitive (54.4%) or physical (37.5%) functioning; 30% of grants incorporated an aging‐related biomarker. Few grants focused on racial and ethnic minority (3.0%) or rural cancer survivors (2.4%). Conclusions: This portfolio analysis showed an increase in the number of NIH‐funded grants focused on cancer survivors and accelerated aging, but notable gaps are evident. Given the rapidly growing survivor population, many of whom will experience accelerated aging trajectories, there is a critical need to better understand accelerated aging phenotypes and mechanisms, so that those at the highest risk for adverse aging‐related effects can be identified and interventions developed.